Introduction: Addressing the Challenges of Innovation in Sustainable Design and Cultural Reproduction in the Digital Era - Fauzan Mustaffa; Lim Kok Yoong; Amir Shahlan Amiruddin (Wacana Seni Journal of Arts Discourse, 2025)
This special issue brings together eleven interdisciplinary articles that examine the intersections of innovation, sustainability, and cultural heritage in the digital era, offering varied perspectives on the evolving interplay between technology and cultural practice. The collection showcases how emerging tools, including artificial intelligence, human-centred design, and immersive visualisation, are reshaping creative fields, spanning sustainable architecture, interactive museum design, wearable technologies, and digital reinterpretations of myth and identity. Collectively, these contributions illustrate how innovation can serve not only as a driver for sustainable futures but also as a platform for meaningful dialogue on cultural continuity, the enrichment of sensory experience, and the reconnection between ecological and symbolic relationships. By blending practical innovation with critical cultural inquiry, this issue provides a timely and forward-looking platform for scholars and practitioners to reflect on how design and technology can actively contribute to the creation of inclusive, resilient, and culturally rich futures.